The human cytomegalovirus UL98 gene transcription unit overlaps with the pp28 true late gene (UL99) and encodes a 58-kilodalton early protein. - Adam, B L (1995)
A murine monoclonal antibody (I2) reacts strongly with the nucleus of human cytomegalovirus (HCMV)-infected human fibroblasts. Western blot (immunoblot) analysis using I2 demonstrated that a protein with an apparent molecular mass of 58-kDa (E58) was expressed at 5 h after infection, and levels increased through 72 h. Immunoblot screening of an early cDNA expression library resulted in a positive clone which hybridized to the right end of the XbaI C fragment of the HCMV Towne strain. Further analysis demonstrated that the E58-specific clone was homologous to the putative UL98 open reading frame, which has been proposed to encode the viral alkaline exonuclease homolog. RNA analysis demonstrated a 3.0-kb RNA which is expressed at early times after infection, as well as in the absence of viral DNA replication, and which is 3' coterminal with the pp28 (UL99) gene region. Insertion of the UL98 genomic sequence into a eucaryotic expression vector and subsequent Western blot analysis using I2 demonstrated that the expressed protein comigrated with E58 from infected cells. E58 also reacts specifically with a previously described antibody, anti-P2-1, which was proposed to recognize a putative late 58-kDa protein. E58 comigrates with the putative late 58-kDa protein, indicating that these two proteins are likely the same. Analysis of the UL98 promoter revealed a TATATAA sequence located at nucleotide 142525. Insertion of the putative promoter 5' to a reporter gene demonstrated that the UL98 promoter was activated in cotransfection experiments with IE1 and IE2 proteins. These studies demonstrate that UL98 is a bona fide early gene, which is consistent with its probable role as the viral alkaline exonuclease gene.